The Effect of Hots-Oriented Worksheets on Heat and Kinetic Theory of Gases on Students' Critical and Creative Thinking Ability with Guided Inquiry Model in Grade XI SMA Al-Istiqamah Pasaman Barat - Hilmi Rizki Anjani; Silvi Yulia Sari; Yenni Darvina; Letmi Dwiridal (Universitas Negeri Padang, 2021)
This research aims to see how effect of HOTS-oriented worksheets on heat and kinetic theory of gases on students' critical and creative thinking ability with guided inquiry model in grade XI SMA Al-Istiqamah Pasaman Barat. The type of research used is quasi-experimental. In this research, two classes were used as the sample class, where class XI IPA 1 was the experimental class and class XI IPA 2 was the control class. The difference in treatment between the two classes is that in the experimental class the product given is HOTS-oriented worksheets while in the control class the product given is conventional student worksheets in schools. For the treatment equation in the two classes, the learning model used is the guided inquiry learning model. The technique for collecting data was a written test with HOTS oriented questions. Critical and creative thinking skills are the basis for assessment in this research. The results of the study after being given treatment in both classes found that the highest skill score between the two classes was the value obtained by the experimental class. Based on the research that has been done, it is concluded that after being given treatment to the sample class, there is an increase in students' critical and creative thinking skills for each indicator. The improvement of students' critical and creative thinking skills on each indicator got higher results in the experimental class than the control class.